Agro Climatic Feasibility Rosa damascena mill Cultivation in Climate Change Condition in northern part of Isfahan Province Zahra sadat Jalali Chiomeh - zahra sadat Jalali Chimeh; Amir Gandomkar; Morteza Khodagholi; Hossein Battoli (تحقیقات کاربردی علوم جغرافیایی)
Agriculture, as one of the most important human economic activities, is closely related to the climatic conditions, and any changes in the climatic conditions can have dramatic changes in agriculture. The main objective of this study is to investigate the spatial changes of the Agro Climatic Feasibility Rosa damascena mill Cultivation in Climate change Condition in northern part of Isfahan province including Kashan, Natanz, Ardestan and Aran Bidgol, under the four carbon dioxide emission pathways (RCPs)of 2050.  Two groups of factors involved in agroclimatic feasibility of Rosa damascena mill cultivation including environmental factors (topography, soil) and climatic factors were extracted. Based on these factors, suitable zones of Rosa damascena mill cultivation, were identify using Fuzzy gamma function. In the next step, by simulating the climatic elements of the region in 2050, under the four carbon dioxide emission pathways, the fifth report of the IPCC, replacing the simulated climatic variables of 2050 under the four lines, by re-implementing the fuzzy gamma function, favorable areas of cultivation Rosa damascena mill was identified in each region in each scenario. In the next step, by simulating the climatic elements of the region in 2050, under the four carbon dioxide emission pathways, the fifth report of the IPCC, replacing the simulated climatic variables of 2050 under the four lines, by re-implementing the fuzzy gamma function, favorable areas of cultivation The Rosa damascena mill was identified in each region in each scenario. The results showed that in the base period climate, about 0.33% of the area (9025 km2) has a climate suitable for cultivating Rosa damascena mill and more than 67% of the area of ​​the region has a weak talent. The results of the simulation of the climatic conditions of 2050 under four carbon dioxide emission lines indicate that, under all scenarios, favorable areas for cultivating Rosa damascena mill in the studied area have increased. In the trajectory of 8/8 release, the highest class of agro-colliery was the cultivation of the flowers of Mohammadi gardens